Biopsychosocial and Spiritual Implications of Patients With COVID-19 Dying in Isolation - Galbadage, Thushara; Peterson, Brent M.; Wang, David C.; Wang, Jeffrey S.; Gunasekera, Richard S. (Frontiers in Psychology, 2020)
Critically ill patients with the Coronavirus disease 2019 (COVID-19) are dying in isolation without the comfort of their family or other social support in unprecedented numbers. Recently, healthcare teams at COVID-19 epicenters have been inundated with critically ill patients. Patients isolated for COVID-19 have had no contact with their family or loved ones and may have likely experienced death without closure. This situation highlights concerns about patients' psychological and spiritual well-being with COVID-19 and their families, as they permanently part ways. While palliative care has advanced to adequately address these patients' needs, the COVID-19 pandemic presents several barriers that force healthcare teams to deprioritize these essential aspects of patient care. The severe acute respiratory syndrome (SARS) outbreak in 2003 gave us a glimpse of these challenges as these patients were also isolated in hospitals. Here, we discuss the importance of the biopsychosocial spiritual model in end-of-life care and its implications on patients dying with COVID-19. Furthermore, we outline an integrative approach to address the unique and holistic needs of critically ill patients dying with COVID-19. These include intentional and increased coordination with trained palliative care staff, early and frequent goals of care including discussion of end-of-life plans, broader use of technology to improve connectedness, and shared decision making with patients' families.